2019
DOI: 10.3389/fimmu.2019.02975
|View full text |Cite
|
Sign up to set email alerts
|

Labile Heme Aggravates Renal Inflammation and Complement Activation After Ischemia Reperfusion Injury

Abstract: Background: Ischemia reperfusion injury (IRI) plays a major role in solid organ transplantation. The length of warm ischemia time is critical for the extent of tissue damage in renal IRI. In this experimental study we hypothesized that local release of labile heme in renal tissue is triggered by the duration of warm ischemia (15 vs. 45 min IRI) and mediates complement activation, cytokine release, and inflammation. Methods: To induce IRI, renal pedicle clamping was performed in male C57BL/6 mice for short (15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Accordingly, studies from Nath and colleagues have shown a detrimental role of heme released from hemoproteins in kidney injury [98][99][100]. Furthermore, in an experimental model of renal ischemia-reperfusion injury (IRI), we recently detected high levels of local labile heme in kidneys, which was dependent on the IRI-time and correlated with the IRI-mediated inflammation [101]. The source of heme in this setting is currently not clear but indicates that extracellular labile heme might aggravate an inflammatory response [101].…”
Section: Heme As a Pro-inflammatory Signal In Macrophagesmentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, studies from Nath and colleagues have shown a detrimental role of heme released from hemoproteins in kidney injury [98][99][100]. Furthermore, in an experimental model of renal ischemia-reperfusion injury (IRI), we recently detected high levels of local labile heme in kidneys, which was dependent on the IRI-time and correlated with the IRI-mediated inflammation [101]. The source of heme in this setting is currently not clear but indicates that extracellular labile heme might aggravate an inflammatory response [101].…”
Section: Heme As a Pro-inflammatory Signal In Macrophagesmentioning
confidence: 86%
“…Furthermore, in an experimental model of renal ischemia-reperfusion injury (IRI), we recently detected high levels of local labile heme in kidneys, which was dependent on the IRI-time and correlated with the IRI-mediated inflammation [101]. The source of heme in this setting is currently not clear but indicates that extracellular labile heme might aggravate an inflammatory response [101]. Alternatively, labile heme levels in the intravascular space might mediate inflammatory effects on macrophages via secondary factors such as complement activation [102,103].…”
Section: Heme As a Pro-inflammatory Signal In Macrophagesmentioning
confidence: 99%
“…Heme toxicity and its pro-inflammatory effects have been demonstrated in experimental disease models like sickle cell disease (SCD), malaria, sepsis, atypical hemolytic uremic syndrome, arteriosclerosis, or ischemia-reperfusion injury ( 27 , 41 , 49 52 ). The damaging effects of free heme can be blocked by intracellular factors like heme oxygenases and ferritin, and extracellular factors such as various plasma proteins, respectively ( Figure 1 ).…”
Section: Heme Interactions With Serum Heme-binding Proteins and Role mentioning
confidence: 99%
“…The period of warm ischemia has a high influence on the induction of IRI-related cellular stress. In a recent study by Wang et al [ 56 ], the cellular responses to two different periods of warm renal ischemia (15 vs. 45 min) were studied. Labile heme concentrations in renal tissue were significantly higher after prolonged warm ischemia (45 min) as compared to short warm ischemia (15 min).…”
Section: Ischemia-reperfusion Injury (Iri)mentioning
confidence: 99%